2014
DOI: 10.1108/jfbm-08-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence in family firms

Abstract: Purpose – Although researchers have highlighted the importance of relational and family factors for the sustainability of a family firm, there is not much empirical research exploring how emotions and the management of emotions play a role in the interpersonal dynamics of family business owners. The purpose of this paper is to explore how the way family members manage their emotions affects the interpersonal dynamics in the family, business, and ownership subsystems of a family firm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…For example, Miao, Humphrey, Qian, and Pollack (2018c) found that emotional intelligence is positively related to entrepreneurial intentions, while Allen, Stevenson, O’Boyle, and Seibert (2020) convincingly demonstrate that emotional intelligence is the most important trait predictor of entrepreneurial success, even more so than cognitive ability or measures of the Big Five personality traits. Although no meta-analysis specifically considers emotional intelligence in family businesses, case studies on family businesses illustrate the many ways that emotional intelligence can benefit family firms (Betancourt, Botero, Ramirez, & Vergara, 2014; Boyatzis & Soler, 2012). Moreover, Shepherd (2009) has convincingly argued that emotional intelligence can help family business members cope with a variety of intense emotions, and can aid grief recovery from the loss of a family business.…”
Section: Emotions In Family Firmsmentioning
confidence: 99%
“…For example, Miao, Humphrey, Qian, and Pollack (2018c) found that emotional intelligence is positively related to entrepreneurial intentions, while Allen, Stevenson, O’Boyle, and Seibert (2020) convincingly demonstrate that emotional intelligence is the most important trait predictor of entrepreneurial success, even more so than cognitive ability or measures of the Big Five personality traits. Although no meta-analysis specifically considers emotional intelligence in family businesses, case studies on family businesses illustrate the many ways that emotional intelligence can benefit family firms (Betancourt, Botero, Ramirez, & Vergara, 2014; Boyatzis & Soler, 2012). Moreover, Shepherd (2009) has convincingly argued that emotional intelligence can help family business members cope with a variety of intense emotions, and can aid grief recovery from the loss of a family business.…”
Section: Emotions In Family Firmsmentioning
confidence: 99%
“…Some of these studies investigated the effects of personality, in general (Pittino et al, 2017), traits inherited from parents (M. Li & Goetz, 2019), CEO narcissism (Rovelli & Curnis, 2021), and emotional intelligence (Betancourt et al, 2014).…”
Section: Review Resultsmentioning
confidence: 99%
“…As propounded by Hess and Bacigalupo (2010) emotionally intelligent leaders in knowledge-based organisations seek to create environments where employees nurture their creative capabilities which are then utilised efficiently towards the goal attainment of the organisation. G omez Betancourt et al (2014) indicated that family members' capability to manage their emotions influences the interpersonal dynamics in family firms at both group and individual levels.…”
Section: Emotions Influencing the Longevity Of Family Businesses And ...mentioning
confidence: 99%
“…The literature on organisational behaviour highlights the fact that management's emotions are influential in the performance of organisations( Gómez Betancourt et al. , 2014, Kotsou et al.…”
Section: Introductionmentioning
confidence: 99%